IFPRI key facts series: Poverty - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
This is the fifth in a series of Key Facts sheets that IFPRI is producing based on the Integrated Household Surveys (IHS). The purpose of the series is to present data relevant to key policy issues on agriculture, food systems, and development topics in Malawi. Other Key Facts sheets will be produced in the near future.